Treatment delay in patients with bladder tumours. Issue 1 (March 1985) - MacArthur, C; Pendleton, L L; Smith, A
Abstract : Previous work has shown that the hospitals are the most important source of delay in treatment of bladder cancer rather than the patient or the general practitioner. We have studied referral of patients for investigation and treatment in the North West Region using data from the cancer registry. Delay in treatment for this disease is appreciably longer than for the other common cancers we have studied. Various factors associated with speed of treatment are discussed.